CORRUPTION CRIMES IN THE 2023 INDONESIAN CRIMINAL CODE VS. THE ANTI-CORRUPTION LAWS: A COMPARATIVE LEGAL ANALYSIS - Rahmat Taufiq Hidayat; Erdianto Effendi; Davit Rahmadan (Universitas Labuhanbatu, 2025)
Corruption Crime (Tindak Pidana Korupsi or Tipikor) poses serious threats to state finances, governance, and public trust, prompting its long-standing classification in Indonesia as an extraordinary crime regulated under Law No. 31 of 1999 in conjunction with Law No. 20 of 2001. The enactment of Law No. 1 of 2023 concerning the Indonesian Criminal Code (KUHP), however, marks a significant shift in the regulatory framework of corruption offenses, including changes in criminal sanctions and the integration of corruption into the general criminal law system. This transformation raises critical concerns regarding the future effectiveness of anti-corruption law enforcement and the consistency of criminal policy. This study aims to compare the regulation of corruption crimes under the 2023 Criminal Code and the Anti-Corruption Law, focusing on offense formulation and sanctioning patterns. Using a normative juridical method with a comparative legal approach, this research analyzes the implications of the regulatory shift for anti-corruption strategies in Indonesia. The findings highlight the need for careful legal harmonization to ensure that the reform of the Criminal Code does not undermine the deterrent function and integrity of corruption law enforcement. Keywords: Legal Comparison; Indonesian Criminal Code 2023; Anti-Corruption Law; Corruption Crime; Criminal Sanctions